THE INFLUENCE OF FINANCIAL LITERACY AND LIFESTYLE ON THE CONSUMER BEHAVIOR OF GRADE XII STUDENTS AT WIDYA MANGGALA VOCATIONAL SCHOOL, JAKARTA - Ramdani, Abdul Hakim; Adawiyah, Robiatul; Taufik, Taufik (LITERATUS, 2024)
This study aims to determine the Influence of Financial Literacy and Lifestyle on the Consumptive Behavior of Class XII Students at SMK Widya Manggala, East Jakarta. The population in this study were class XII students of SMK Widya Manggala in the 2023/2024 academic year. The sampling technique used in this study was purposive random sampling with a total of 79 respondents. Data collection techniques were in the form of questionnaires, interviews, observations and documentation. This study is a quantitative study with the data analysis technique used being multiple regression analysis. The results of the study showed that: (1) There is no significant influence of financial literacy on the consumptive behavior of class XII students of SMK Widya Manggala, East Jakarta. (2)There issignificant influence of lifestyle on the consumer behavior of class XII students of SMK Widya Manggala, East Jakarta. (3) There is a significant influence of financial literacy and lifestyle together on the consumer behavior of class XII students of SMK Widya Manggala, East Jakarta. The determination coefficient (R2) of Financial Literacy and Lifestyle on the Consumer Behavior of SMK Widya Manggala, East Jakarta students is 0.768, which means that 76.8% of the change in the consumer behavior variable is explained by the two independent variables (financial literacy and lifestyle), while the remaining 23.2% is explained by other variables not included in the study.